Habituation Reveals Fundamental Chromatic Mechanisms in Striate Cortex of Macaque - Tailby, Chris (Society for Neuroscience, 2008)
Prolonged viewing of a chromatically modulated stimulus usually leads to changes in its appearance, and that of similar stimuli. These aftereffects of habituation have been thought to reflect the activity of two populations of neurons in visual cortex that have particular importance in color vision, one sensitive to red–green modulation, the other to blue–yellow, but they have not been identified. We show here, in recordings from macaque primary visual cortex (V1), that prolonged exposure to chromatic modulation reveals two fundamental mechanisms with distinctive chromatic signatures that match those of the mechanisms identified by perceptual observations. In nearly all neurons, these mechanisms contribute to both excitation and to regulatory gain controls, and as a result their habituation can have paradoxical effects on response. The mechanisms must be located near the input layers of V1, before their distinct chromatic signatures diffuse. Our observations suggest that the fundamental mechanisms do not give rise to two distinct L–M and S chromatic pathways. Rather, the mechanisms are better understood as stages in the elaboration of chromatic tuning, expressed in varying proportions in all cells in V1 (and beyond), and made accessible to physiological and perceptual investigation only through habituation.